Reappropiation and Contestation of Post-Colonial Space in Rizal Mantovani’s Kuntilanak (Proceeding of the International Conference on Arts and Humanities, 2020)
This paper examines a contemporary Indonesian horror film titled Kuntilanak (2006) in the light of how the film attempts to reappropriate and contest the post-colonial space as an arena of decolonization.  The post-colonial space here refers to historical buildings of the Dutch colonial legacy that can be found all over Indonesia, especially Java island.  Those unfixed and fluid spaces have been re-appropriated, reconstructed, reproduced, negotiated, neglected, and destroyed during the post-colonial period as ongoing attempts to (re)define national identity.  The analysis will focus on a single building that serves as the film set which possesses the characteristic of colonial architecture that represents the former Dutch colonial power.  Horror genre is chosen as it is considered the most appropriate genre to talk about the past in the present and how they are related to each other, as allegorized by the old building and the monster in the film.  The analysis focuses on several aspects of film studies that include mise-en-scene, the narrative, and the film stars which are later related to the politics of space and post-colonial theory.  The findings show that there are intertwined modern and local values that the film offers which lead to hybrid identity.Keywords: post-colonial space, reappropriation, contestation, decolonization
Keywords: Film Studies; Indonesian horror film; post-colonialism